Controlling root rot disease in colored peppers utilizing mixtures of bio-agents or antioxidants with regard to yield qualities - Alqahtani-T, Tahani Alqahtani (Journal of Plant Protection Research, 2026)
Root rot caused by soil-borne fungi severely limits the productivity of colored sweet pepper in Saudi Arabia, challenging the sustainability of intensive greenhouse systems. This study assessed whether mixtures of microbial antagonists, with or without an antioxidant formulation, provided superior suppression of root rot and improvement of fruit quality compared to single applications. Greenhouse and commercial greenhouse experiments evaluated single strains of Trichoderma harzianum, Bacillus subtilis, and Pseudomonas fluorescens, their pairwise mixtures, and their combinations with a potassium tartrate-based antioxidant over two consecutive growing seasons. All biocontrol combinations significantly reduced disease incidence relative to the untreated control and increased marketable yield. The T. harzianum + B. subtilis mixture provided the greatest disease suppression and highest fruit yield, followed by T. harzianum + P. fluorescens. When B. subtilis was combined with an antioxidant, it produced the strongest reductions in root rot incidence. Treatments most effectively suppressing disease also enhanced total phenolic content, total soluble solids (TSS), and vitamin C (V.C.) concentration in fruits, which correlated positively with improved disease resistance and yield. These findings demonstrated that integrating compatible biocontrol agents, particularly Bacillus subtilis, with antioxidants can offer a promising and environmentally sound strategy for managing pepper root rot while simultaneously improving fruit nutritional quality in greenhouse production systems in Saudi Arabia.